CULTURAL COMMUNICATION THROUGH AUDIO-VISUAL MEDIA (Study of the films Children of Heaven, Color of Paradise, and Baran by Majid Majidi) - A. Rani Usman; Ahmad Fauzan; Azman Sulaiman (Profetik: Jurnal Komunikasi, 2020)
Audio-visual or film is one of the strategic means of intercultural communication.  Films are often used as a medium of propaganda for partisan and partial political interests, leading to misunderstandings of a culture. The destruction of a nation's cultural meanings and values always involves audio-visual media to create psychological effects in building opinion and mobilizing the masses. Iran and its culture are the victims of world misunderstanding. However, the films directed by Iranian filmmakers have opened a ‘cultural dialogue’ with dignity and in an artistic manner. This study aimed to examine Iranian cultural communication patterns through cinema and identify Iranian cultural symbols that influence cultural communication. This research used Symbol and Value Theory. Symbols and values influence political and cultural campaigns. This research employed the Gestalt method that involved descriptive coding of sentences and images and recording of contents. Through Gestalt, we can interpret the meaning and behavior displayed by humans in certain situations. The films ‘Children of Heaven’, ‘Color of Paradise,’ and ‘Baran' directed by Majid Majidi, communicate essential aspects of Iranian culture, showing the spirit of resilience of Iranian society today, which is rarely included in the news due to global politics. The representation of Iranian culture is presented in very natural and simple ways without using visual effects. The reproduction of Iranian culture in the three films above uses a measured, intense, and substantive approach and shooting angle. The spirit of Sufism was reflected in the production process and the Iranian cinematic contents.